Performance comparison Amil Zakat Institutions on Ponorogo towards good Amil governance - Fajar Surya Ari Anggara; Ely Windarti Hastuti (Al Tijarah, 2018)
This study is aimed at performance comparison amil zakat Institutions in Ponorogo area towards Good Amil Governance. The type of study used is a qualitative study with a case study approach, where the results of this study conclude that the performance comparison between amil zakat institutions on Ponorogo. Performance measurement is reinforced by several factors, among others: 1). The governance of Amil Zakat Institute is not yet fully professional in its management, 2). The lack of quantity and quality of human resources at each Institute Amil Zakat which the author of review, 3). Lack of public support, especially the existing Muslim community in the countryside (local wisdom). This study aims to find out how the level of performance measurement for Amil Zakat institutions in Ponorogo district will be assessed based on the performance indicator standards issued by Indonesia Magnificence of Zakat. This is important because the potential for managing zakat funds that are so large must be followed by professional management so that Good Governance can be achieved.